Radiographic measurement of bowleg deformity: variability due to method and limb rotation - Stricker, S J; Faustgen, J P (Journal of pediatric orthopaedics, 1994)
In evaluation of bowlegs, the tibiofemoral axis (TFA) and the proximal tibial metaphyseal-diaphyseal angle (MDA) are commonly measured, but both are subject to measurement error. In this study, we determined the intraobserver errors for the MDA and TFA, comparing several different measurement techniques. We also determined the variability of these angles caused by 15 degrees and 30 degrees of external rotation of the knee. We noted that limb malrotation may affect the measurement variability of these angles significantly, especially the TFA. To minimize radiographic measurement error, the clinician must ensure neutral limb rotation and uniform measurement technique.